Odpowiedzi

2010-03-30T15:08:15+02:00
2y+3x=14
3x-6y=0

3x+2y=14
3x-6y=0

-3x-2y=-14
3x-6y=0

-8y=-14
y=14/8 = 1 6/8



0,2x+0,3y=1
½x-2y=-3

x+1,5y=1
x-4y=-6

x+1,5y=1
-x+4y=6

5,5y=7
y=7/5,5 = 1 1,5/5,5

2010-03-30T15:10:52+02:00
2y+3x=14
3x-6y=0

3x+2y=14
3x-6y=0

-3x-2y=-14
3x-6y=0

-8y=-14
y=14/8 = 1 6/8



0,2x+0,3y=1
½x-2y=-3

x+1,5y=1
x-4y=-6

x+1,5y=1
-x+4y=6

5,5y=7
y=7/5,5 = 1 1,5/5,5


2010-03-30T15:13:23+02:00
2y+3x=14
3x-6y=0 /*(-1)

2y+3x=14
6y-3x=0
---------------- +
8y=14 /:8
y=1,75

2*1,75+3x=14
3,5+3x=14
3x=14-3,5
3x=10,5 /:3
x=3,5
y=1,75

b)
0,2x+0,3y=1
1/2x-2y=-3

0,2x+0,3y=1 /*5
0,5x-2y=-3 /*(-2)

x+1,5y=5
-x+4y=6
---------------- +
5,5y=11/ :5,5
y=2

x+1,5*2=5
x=5-3
x=2
y=2